Therapy for involuting infantile hemangioma: Propranolol effectiveness - Luz Orozco-Covarrubias; Leticia Lara-Mendoza; Luis Martín Garrido-García; Ramón Ruiz-Maldonado (Wolters Kluwer Medknow Publications, 2018)
Background/Objectives: The efficacy of propranolol as a treatment for infantile hemangiomas (IHs) has been documented. Until now, little has been written about the role of propranolol beyond the proliferation phase of IH. Our aim was to document propranolol efficacy and safety in the treatment of involutive IH. Patients and Methods: Two evaluations were conducted. Investigators evaluated the final clinical results by comparing clinical data at baseline and at the end of the study. Evaluators scored each panel of photographs and were blinded from any clinical information. Both groups used the same scoring system. Patients treated with propranolol in our department between 2009 and 2014 were reviewed. Results: A total of 15 patients with involuting IH treated with propranolol were eligible. Eleven (73%) were females, ranging in age between 16 and 110 months (median 41 months). The types of IH were mixed (n = 13) and superficial (n = 2). The median duration of the propranolol treatment was 20 months (range 6-33 months). The mean size reduction was from 6 cm ± 4.33 before the treatment to 3.98 ± 1.25 at the end of the treatment. The general mean involution according to the investigators' evaluation was 4.1 ± 2.7. The general mean involution according to the evaluators' evaluation was 4.9 ± 1.5. Telangiectasias showed no response. Recurrence was observed in one patient. Transient nightmares were documented in one patient, and nighttime awakenings were documented in another. The therapy was discontinued in neither of these patients. Conclusions: In our experience, propranolol was well tolerated and associated with limited adverse reactions. The use of oral propranolol was effective in the treatment of IH beyond the proliferative phase.